Bordering the postcolonial state: the relevance of Sikkim in India's support for Indonesia's occupation of East Timor. Issue 2 (29th April 2022) - Strating, Rebecca; Davis, Alexander E.
ABSTRACT: In 1975, two small territories with distinct identities were incorporated within larger postcolonial states: in April, the Himalayan kingdom of Sikkim became a state within the Republic of India, while in December, the Republic of Indonesia annexed Portuguese (East) Timor. From 1975 to 1982, India voted against all United Nations General Assembly resolutions supporting East Timor's self-determination. While Western states' support is well documented, scant attention has been paid to India's role, which sits in contrast to almost all other non-aligned, postcolonial states. This paper seeks to understand India's support for Indonesia. We argue that India's support was due to similarities in key ideas that shaped India and Indonesia's state construction, which remained despite the ways in which the relationship had soured in the preceding decades. We draw this argument out by comparing the narratives India used to justify its incorporation of Sikkim with those of Indonesia in East Timor.